ICT as a Supporting Factor for Innovation Activities (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Development and usage of information and communication technology (ICT) is continuously growing in the last 30 years. The main reason is that ICT has a great potential to improve the efficiency of business processes, to increase the competitiveness, but also to facilitate and drive innovations. Innovation has become a crucial factor for the economic development and ICT offer great opportunities in supporting innovation activities. The goal of the paper is to identify the influence of the usage of the ICT on the innovation activities in European countries. Data for the period of five years (2007-2011) were collected from the European statistical database – Eurostat and Global Competitiveness Report. In order to investigate the ICT impact on the Innovation and sophistication factor subindex of the European countries, we conducted a panel regression analysis. Research results showed that ICT support innovation activities. However, the ICT has the highest impact on the 11th pillar: Business sophistication of the Global Competitiveness Index.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.